A longitudinal study of MNE innovation: the case of Goodyear. Issue 3 (19th August 2014) - Scalera, Vittoria Giada Giada; Mukherjee, Debmalya; Perri, Alessandra; Mudambi, Ram; Rugman, Alan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The ability to innovate constantly amidst a turbulent and competitive environment is often the key force behind multinational enterprise (MNE) survival and dominance. In this article, we provide insights into the innovation trajectory, and knowledge pipelines of mature industry MNEs. Design/methodology/approach We conduct an in-depth longitudinal study of the Goodyear Tire and Rubber Company, a global manufacturing company in the tire and rubber industry. Our findings are based on USPTO patent and trademark data from 1975-2005. Findings The analysis reveals three crucial trends: (1) the major role of continuous investment in innovation in the firm's survival and turnaround; (2) the evolution of the firm's innovation network from a headquarters-centric model towards more geographical dispersal, and (3) the changing mix of innovation from traditional "hard" science-based research towards a greater emphasis on "softer" competencies in design and trademarks. This third trend in particular opens up important new avenues for research on MNE innovation practices. Originality/value In this study, we integrate historical analysis of a single firm in the context of its changing industry environment. The historical analysis is enriched by a detailed longitudinal, quantitative analysis using a variegated dataset of patents and trademarks to investigate innovation.